Asymmetric Information in Agriculture Supply Chain Management: A Literature Review - Abdulaziz Mardenli; Dirk Sackmann (ExcelingTech, 2022)
Food markets have been in a state of upheaval for some time now. Due to the current trend of numerous consumers favouring sustainable nutrition, the organic food market has proven to be an important market for both consumers and producers. This development enables consumers to continue to afford sustainable food in the future. Due to the complexity and non-transparency of value chains (especially in the organic food market) as well as the insufficient labelling of organic food, there is a lack of information in the organic food market. This often results in market failure. The aim of this research is to understand the problems caused by asymmetric information in the food supply chain and to present the principal-agent theory to detect and describe asymmetric information and as an economic model for understanding asymmetric information in the food supply chain. The principal-agent theory is most frequently used to explain and describe asymmetric information. The imperfection of principal-agent theory is due to the lack of and insufficient application of theories from related disciplines such as transaction theory and game theory. Furthermore, the theory assumes the existence of an informed agent and an uninformed principal. Finally, the analysis of information asymmetry is based on the existence of only principal and agent and neglects the information asymmetries in multi-level network-value chains. This paper presents a structured literature review that provides an overview of the current literature on the subject of asymmetric information in multi-level network-value chains. The identified studies are classified, and gaps are identified for future research.